A study on status of Al-Jalalah on catfish "Clarias gariepinus" and its impact to Malaysia aquaculture industry - Nurul Solehah Ahmad (International Institute for Halal Research and Training, International Islamic University Malaysia, 2018)
The consumption of Halal foods and goods is compulsory to all Muslims. Lack of knowledge, awareness and understanding of the Halal concept among Muslims and the manufacturers of Halal products may cause the loss of appreciation to Halal especially in Aquaculture industry. The basic issue in Halal food production is cleanliness, free from ‗contamination' and healthy food as defined in the Quran. Halal means permissible and lawful while Haram means prohibited. Mashbooh is something questionable or doubtful, either due to the differences in scholars' opinions or the presence of undetermined ingredients in a food product. There are many issues on feeding animal with unclean food or unnature feed to the animals. For example issue on the status of catfish (Clarias batrachus, Linnaeus), which fed with filth or najs and catfish (Pangasius hypopthalmus) fed with feed derived from pig organs in several ponds at Batu Gajah, Tronoh and Papan, Perak. In 2010, The Straits Times dated 11 April 2010 reported that there were allegations on employers of catfish in Agrotech Park Smart Jaya, Kuala Selangor state that the non-Malay catfish entrepreneurs feed the waste, carcasses and internal organs of pigs. As in many farms, it is quite common to include a protein supplements in the animal feed. The practice is not limited to major farms, also labelled as factory farms. The protein supplements may be used by farmers who claim to raise their poultry and cattle on the ranges where the animals roam freely, know as free- range farms. These protein supplements are made from slaughterhouse by – products and others ingredients. Additionally, In fiqh, according to Sayyid al-Bakri says in I'anat al-Talibin the technical name for animals that eat impurities are 'Jallalah' which is contaminated animals because they eat 'Jalla' means contaminant or impurity. From this research, one guideline have been organize for Al-Jallalah animal. It can be used for halal authentication called as ―the standard of Al-Jallalah animal and measured by physical (changeable, not changeable), structure and protein, external factor (environment), water flow and animal feed. The elements for Jallalah animal is transform, changes, impurity and contaminated. The analysis process that being used in this research is deductive and inductive concept. Deductive is any conceptual from linguistic and meanings taken as definition. Inductive is a conclusion of general ruling which is generated from special fact especially on the problem that do not have the origin from al-Quran and hadith. This study will discuss the concept of Al-Jallalah animals, the elements, its components and the issues related with Al-Jallalah animals also fatwa released by the National Fatwa Council. Hence, it should be emphasized here that the issue of food is an important thing in Islam and must be seriously considered by every individual Muslim because it involves physical and spiritual development.